(untitled) (International Journal of Communication Systems and Network Technologies, 2021)
A person who is unable to speak or hear relies solely on sign language to communicate. People who are physically unable can use sign language to express their thoughts and feelings. In order to identify alphabets and movements in sign language, a novel technique is proposed in this work. We can identify the clues using computer vision and neural networks and output the right text.